Problems of Appointing Party Leaders as State Ministers in the Indonesian Constitutional System - Radytia, Moch (International Journal of Business, Law, and Education, 2024)
Indeed, the stability in running the wheels of government using the presidential system is very promising. However, at present, in Indonesia, the presidential system of government is not maximized, this is because the presidential system of government that is applied has been collaborated with a multi-party system. The application of the system is not maximized as evidenced in the formation of the cabinet, namely the selection of ministers by the president is only used as a forum for "compromise" with his coalition political parties during the election battle. Furthermore, the issue of the appointment of political party leaders as state officials is not only a matter of political interest and power, but also a matter of violation of the provisions of Law Number 39 of 2008 concerning State Ministries. Prerogative rights as the basis for the president in appointing state ministers and forming the cabinet should still be based on the provisions of the applicable laws and regulations. Because the president's disorderly use of his prerogative will lead to his impeachment as president. The implementation of a presidential system of government combined with a multi-party system will continue to experience problems in the appointment of state ministers by the elected president and vice president. Thus, the prerogative right, which is essentially the absolute authority of the president, has now been reduced. Thus, the appointment of a minister who also serves as a leader of a political party should pay attention to the provisions of Law Number 39 of 2008 concerning the Ministry of State and Law Number 2 of 2008 concerning Political Parties as well as Law Number 2 of 2011 concerning Amendments to Law Number 2 of 2008 concerning Political Parties.